Histopathological landmarks of hepatocellular carcinoma in Malaysians - Cheah, P.L.; Looi, L.M.; Nazarina, A.R.; Goh, K.L.; Rosmawati, M.; Vijeyasingam, R. (2003)
A study was conducted at the Department of Pathology, University of Malaya Medical Centre, Kuala Lumpur into the histological type (WHO classification), grade (modified Edmondson and Steiner’s grading system), mitotic rate, bile production, hyaline globule and Mallory hyaline formation of 52 cases of hepatocellular carcinoma (HCC) diagnosed during a 13-year period between 1st January 1990 to 31st December 2002. In addition, associated cirrhosis, dysplasia (large liver cell dysplasia: LLCD and small liver cell dysplasia: SLCD) and microvascular permeation were also looked for whenever the situation permitted. The patients’ ages ranged from 21-years to 85-years (mean = 58.7 years) with a predilection for males and Chinese. Histologically, majority (73.1%) of the tumours demonstrated a trabecular pattern of growth. The bulk (73%) of the tumours were either of grade II or III differentiation. Mitotic activity ranged between 0-100/10 high power fields (hpf) with a mean of 22.2/10 hpf. Bile was noted in 25%, hyaline globules 17.3% and Mallory bodies in one case. Concomitant cirrhosis was present in 73.5%. 73.5% of the cases had associated LLCD. 5 with LLCD also showed SLCD. Microvascular permeation was shown in 76.2% of cases. On comparison with findings from other studies, no major difference seems to exist between the histological characteristics of our HCC cases and that of other populations.